Tardigrada nova: a bibliographic analysis and catalogue of new species described in Zootaxa before 2006 - Zhang, Zhi-Qiang (Zootaxa, 2006)
During 2002 to 2005, 35 papers on Tardigrada were published in Zootaxa by 22 authors from nine countries with descriptions of 33 new species. A bibliographic analysis of these papers is presented here along with a catalogue of new species of Tardigrada described in these papers.